Development of a dynamic user interface for an electronic device descriptions interpreter for intelligent sensors; Молодежь и современные информационные технологии - Pushkarskiy R. V. (2025, 2025)
To solve the problem of supporting intelligent sensors manufactured in the Russian Federation by foreign software, ASPECT LLC has developed the Colibri Field Data Bus Server. This software allows to work with HART- and Colibri-based devices with support of their electronic descriptions (CDD/EDD). The software facilitates dynamic GUI based on CDD/EDD, offering advanced control and diagnostic capabilities for field equipment